Battery monomer, battery device and electric equipment

By adding a specific proportion of solvents and additives to the electrolyte of the battery cell, the problem of HF corrosion of the SEI film in lithium iron phosphate batteries is solved, and the circulation and fast charging performance of the battery are improved.

CN120127218AActive Publication Date: 2025-06-10CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510621111.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-02
Filing Date
2025-05-14
Publication Date
2025-06-10
Estimated Expiration
2045-05-14

AI Technical Summary

Technical Problem

The HF generated by lithium iron phosphate system batteries during circulation will corrode the SEI film on the negative electrode surface and reduce the cycle life of the battery.

Method used

A battery cell is adopted, including an electrode assembly and an electrolyte. In the electrode assembly, the positive electrode sheet comprises a positive current collector and a positive electrode active material layer. A specific proportion of the first solvent, the first additive and the second additive are added to the electrolyte to reduce the generation of HF and corrosion of the SEI film.

Benefits of technology

Effectively reduce the corrosion of HF on the SEI film, improve the circulation performance of the battery cell, improve the transmission rate of lithium ions, and improve the fast charging performance of the battery cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120127218A_ABST
    Figure CN120127218A_ABST
Patent Text Reader

Abstract

The invention provides a battery monomer, a battery device and electric equipment, the battery monomer comprises an electrode assembly and an electrolyte, and the electrode assembly comprises a positive pole piece; the electrolyte comprises a first solvent, the first solvent comprises one or two of ethylene carbonate and propylene carbonate, and based on the total mass of the electrolyte, the mass ratio of the first solvent is 20%-40%; the first additive comprises one or two of vinylene carbonate and an ethylene carbonate derivative, and the mass ratio of the first additive is 1%-8% based on the total mass of the electrolyte; the electrolyte comprises a first additive and a second additive, the second additive comprises a compound shown as a formula I: R1-COOLi, R1 comprises any one of hydrogen atoms, halogen atoms, C1-C5 alkyl groups and C1-C5 halogenated alkyl groups, and the mass ratio of the second additive in the electrolyte is 0.5%-5% based on the total mass of the electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross - Reference to Related Applications This application claims the priority of PCT patent application PCT / CN2025 / 086927 titled "Battery Cell, Battery Device and Electrical Equipment" filed on April 2, 2025, and the entire content of this application is incorporated herein by reference. Technical Field

[0002] This application relates to the field of batteries, and specifically, to battery cells, battery devices, and electrical equipment. Background Art

[0003] Batteries are not only applied to energy storage power systems such as hydropower, thermal power, wind power, and solar power plants, but also widely used in electric transportation such as electric bicycles, electric motorcycles, and electric vehicles, as well as in multiple fields such as military equipment and aerospace. HF generated during the cycling of lithium iron phosphate-based batteries will corrode the solid electrolyte interface (SEI film) on the surface of the negative electrode, reducing the cycle life of the battery. Summary of the Invention

[0004] In a first aspect of this application, a battery cell is provided. The battery cell includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode tab, where, the positive electrode tab includes a positive electrode current collector and a positive electrode active material layer provided on at least one side of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes a lithium-containing phosphate; the electrolyte includes: a first solvent, the first solvent includes one or both of ethylene carbonate and propylene carbonate. Based on the total mass of the electrolyte, the mass ratio of the first solvent is 20% - 40%; a first additive, the first additive includes one or both of vinylene carbonate and ethylene carbonate derivatives. Based on the total mass of the electrolyte, the mass ratio of the first additive is 1% - 8%. The ethylene carbonate derivative includes a compound represented by Formula II: Formula II, wherein, R 1 , R 2 , R 3 , R 4 each independently includes any one of a hydrogen atom, a halogen atom, an alkyl group with 1 - 5 carbon atoms, and a halogenated alkyl group with 1 - 5 carbon atoms, and R 1 , R 2 , R 3 , R 4 are not simultaneously hydrogen atoms; A second additive, the second additive comprising a compound represented by formula I: R 1 -COOLi Formula I, wherein R 1 comprises any one of a hydrogen atom, a halogen atom, a C1-C5 alkyl group, and a C1-C5 haloalkyl group. Based on the total mass of the electrolyte, the mass percentage of the second additive in the electrolyte is 0.1% - 4%.

[0005] The battery cell proposed in this application can reduce the corrosion of the SEI film by HF, improve the cycling performance of the battery cell, and at the same time, can improve the lithium ion transmission rate and the fast charging performance of the battery cell.

[0006] According to some embodiments of this application, based on the total mass of the electrolyte, the mass percentage of the second additive is 0.5% - 2%. Thus, while combining with H 2 O, the viscosity of the electrolyte is reduced.

[0007] According to some embodiments of this application, the second additive comprises one or more of lithium acetate, lithium difluoroacetate, and lithium trifluoroacetate. Thus, the hydrolysis of LiPF 6 and the generation of HF are reduced, and the corrosion of the SEI film is reduced.

[0008] According to some embodiments of this application, the second additive comprises lithium trifluoroacetate. Thus, after polyfluoro substitution, the acidity of the second additive is weakened, and the corrosion of the aluminum foil can be reduced.

[0009] According to some embodiments of this application, the electrolyte further comprises a second solvent, and the second solvent comprises one or two of a carboxylic ester solvent and a chain carbonate solvent. Thus, the conductivity of the electrolyte is improved.

[0010] According to some embodiments of this application, based on the total mass of the electrolyte, the mass percentage of the second solvent is 45% - 65%. Thus, the conductivity of the electrolyte is improved.

[0011] According to some embodiments of this application, the carboxylic ester solvent comprises a compound represented by formula III: Formula III, wherein R 5 comprises any one of a hydrogen atom, a halogen atom, a C1-C5 alkyl group, and a C1-C5 haloalkyl group, and R 6 comprises any one of a C1-C5 alkyl group and a C1-C5 haloalkyl group. Thus, the carboxylic ester solvents of the above types have a relatively small molecular weight, can improve the ionic conductivity of the electrolyte, and improve the rate performance of the battery cell.

[0012] According to some embodiments of the present application, the carboxylic ester solvent includes one or more of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, and ethyl butyrate. Thus, the carboxylic ester solvents of the above types have a relatively small molecular weight, which can improve the ionic conductivity of the electrolyte and the rate performance of the battery cell.

[0013] According to some embodiments of the present application, the chain carbonate solvent includes one or more of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. Thus, the viscosity of the electrolyte is reduced, and the ionic conductivity of the electrolyte is improved.

[0014] According to some embodiments of the present application, when the second solvent includes a chain carbonate solvent, based on the total mass of the electrolyte, the mass ratio of the first additive is 1% - 3%. Thus, the film-forming impedance is reduced.

[0015] According to some embodiments of the present application, the second solvent includes a carboxylic ester solvent and a chain carbonate solvent. Based on the total mass of the electrolyte, the mass ratio of the carboxylic ester solvent is 8% - 60%, and the mass ratio of the first additive is 3% - 8%. Thus, more additives can participate in film formation, improving the stability of the negative electrode interface and reducing the side reactions between the electrolyte and the negative electrode interface.

[0016] According to some embodiments of the present application, the electrolyte further includes a lithium salt, and the lithium salt includes one or two of lithium fluorosulfonylimide salt and lithium hexafluorophosphate. Thus, the ionic conductivity of the electrolyte is improved.

[0017] According to some embodiments of the present application, based on the total mass of the electrolyte, the mass ratio of the lithium salt is 10% - 18%. Thus, while improving the ionic conductivity of the electrolyte, the viscosity of the electrolyte is reduced.

[0018] According to some embodiments of the present application, based on the total mass of the electrolyte, the mass ratio of the lithium fluorosulfonylimide salt is 4% - 6%. Thus, the migration rate of lithium ions is improved.

[0019] According to some embodiments of the present application, the lithium fluorosulfonylimide salt includes one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium perfluorobutanesulfonylimide. Thus, the migration rate of lithium ions is improved.

[0020] According to some embodiments of the present application, the electrolyte further includes a third additive, and the third additive includes one or more of a sulfur-containing additive and a lithium salt additive. Thus, the cycle performance and fast charging performance of the battery cell are improved.

[0021] According to some embodiments of the present application, the sulfur-containing additive includes one or more of vinylene sulfate, divinylene sulfate, 1,3-propane sultone, butene sulfite, ethylene sulfite, and methylene methanedisulfonate. Thereby, the impedance of the battery cell is reduced, and the fast charging performance of the battery cell is improved.

[0022] According to some embodiments of the present application, the mass ratio of the sulfur-containing additive is 0-2%. Thereby, while reducing the impedance of the battery cell, the gas generation of the battery cell is reduced.

[0023] According to some embodiments of the present application, based on the total mass of the electrolyte, the mass ratio of the sulfur-containing additive is 0.5%-2%. Thereby, while reducing the impedance of the battery cell, the gas generation of the battery cell is reduced.

[0024] According to some embodiments of the present application, the lithium salt additive includes one or more of lithium difluorophosphate, lithium difluorooxalate borate, lithium tetrafluoroborate, and lithium bis(oxalato)borate. Thereby, the gas generation of the battery cell under high temperature conditions is reduced.

[0025] According to some embodiments of the present application, based on the total mass of the electrolyte, the mass ratio of the lithium salt additive is 0-1%. Thereby, while reducing the gas generation of the battery cell, the film formation impedance is reduced.

[0026] According to some embodiments of the present application, based on the total mass of the electrolyte, the mass ratio of the lithium salt additive is 0.2%-1%. Thereby, while reducing the gas generation of the battery cell, the film formation impedance is reduced.

[0027] According to some embodiments of the present application, the lithium-containing phosphate includes: a matrix; a first coating material, the first coating material is located on at least part of the surface of the matrix, and the first coating material contains carbon elements. Thereby, the conductivity of the lithium-containing phosphate is improved.

[0028] According to some embodiments of the present application, based on the total mass of the lithium-containing phosphate, the mass ratio of the carbon element is 0.8%-2.3%. Thereby, while improving the conductivity of the lithium-containing phosphate, the loading of the lithium-containing phosphate on the positive electrode sheet is increased, and the energy density of the battery cell is increased.

[0029] According to some embodiments of the present application, the first coating material includes the compound shown in Formula IV: Li 3-d1 Fe 2-d1 M1 d1 (PO m1 ) n1 Formula IV, Among them, 0 ≤ d1 ≤ 1, 3 ≤ m1 ≤ 5, 2 ≤ n1 ≤ 4, and M1 includes one or more of Ti, Zr, Hf, Ge, and Sn. Thereby, the ionic conductivity and specific capacity of the positive electrode active material are improved, and the fast charging performance and energy density of the battery cell are improved.

[0030] According to some embodiments of the present application, the matrix includes a compound shown in Formula V: Li x1 A y1 Me a1 M2 b1 P 1-c1 X c1 Y z1 Formula V, wherein, 0.5 ≤ x 1 ≤ 1.3, 0 ≤ y 1 ≤ 1.3, 0.9 ≤ x 1 +y 1 ≤ 1.3; 0.9 ≤ a 1 ≤ 1.5, 0 ≤ b 1 ≤ 0.5, 0.9 ≤ a 1 +b 1 ≤ 1.5; 0 ≤ c 1 ≤ 0.5; 3 ≤ z 1 ≤ 5; wherein, A includes one or more of Na, K, and Mg; Me includes one or more of Mn, Fe, Co, and Ni; M2 includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X includes one or more of Cl, C, and N; Y includes one or more of O and F. Thereby, the cycle performance and safety of the battery cell are improved.

[0031] According to some embodiments of the present application, the matrix includes one or more of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium nickel phosphate, and lithium cobalt phosphate. Thereby, the cycle performance and safety of the battery cell are improved.

[0032] According to some embodiments of the present application, when the battery cell is in a 0% state of charge, the tap density of the positive electrode sheet is 2.46 g / cm 3 -2.8 g / cm 3 . Thereby, the energy density of the battery cell is improved.

[0033] According to some embodiments of the present application, the single-sided coating weight of the positive electrode active material layer is 200 mg / 1540.25 mm 2 -400 mg / 1540.25 mm2 Thereby, the energy density of the battery cell is increased.

[0034] According to some embodiments of the present application, the electrode assembly further includes a negative electrode tab, the negative electrode tab includes a negative electrode current collector and a negative electrode active material layer provided on at least one side of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes one or two of a carbon-based material and a silicon-based material. Thereby, the energy density and cycle performance of the battery cell are improved.

[0035] According to some embodiments of the present application, the carbon-based material includes graphite. Thereby, the cycle performance of the battery cell is improved.

[0036] According to some embodiments of the present application, the graphite is a secondary particle formed by aggregation of primary particles, and at least part of the surface of the secondary particle has a second coating material, and the second coating material includes amorphous carbon. Thereby, the side reaction between the negative electrode surface and the electrolyte is reduced, and the cycle performance of the battery cell is improved.

[0037] According to some embodiments of the present application, based on the total mass of the graphite, the mass ratio of the second coating material is 2% - 5%. Thereby, while improving the cycle performance of the battery cell, the energy density of the battery cell is increased.

[0038] According to some embodiments of the present application, the volume average particle size Dv50 of the graphite is 8.5 μm - 14.8 μm. Thereby, the migration path of lithium ions in the solid phase is shortened, and the fast charging ability of the battery cell is improved; at the same time, the side reaction between graphite and the electrolyte is reduced.

[0039] According to some embodiments of the present application, the negative electrode active material includes a silicon-based material, and based on the total mass of the negative electrode active material layer, the mass ratio of silicon element is 0.3% - 5%. Thereby, the energy density of the battery cell is increased.

[0040] According to some embodiments of the present application, the single-sided coating weight of the negative electrode active material layer is 90 mg / 1540.25 mm 2 -185 mg / 1540.25 mm 2 Thereby, the energy density of the battery cell is increased.

[0041] According to some embodiments of the present application, along the length direction of the battery cell, the size of the negative electrode active material layer is larger than the size of the positive electrode active material layer, and the difference between the size of the negative electrode active material layer and the size of the positive electrode active material layer is OH 1;In the width direction of the battery cell, the size of the negative electrode active material layer is larger than that of the positive electrode active material layer, and the difference between the size of the negative electrode active material layer and the size of the positive electrode active material layer is OH 2 , where OH 1 is greater than or equal to OH 2 . Thus, while improving the energy density of the battery cell, lithium deposition on the negative electrode is reduced.

[0042] According to some embodiments of the present application, 1 mm ≤ OH 1 ≤ 4 mm, 1 mm ≤ OH 2 ≤ 3 mm. Thus, while improving the energy density of the battery cell, lithium deposition on the negative electrode is reduced.

[0043] According to some embodiments of the present application, a positive electrode tab is provided on the positive electrode plate, and a negative electrode tab is provided on the negative electrode plate. The positive electrode tab extends along the length direction or the width direction of the positive electrode plate; and / or the negative electrode tab extends along the length direction or the width direction of the negative electrode plate. Thus, the current transmission efficiency is improved, the resistance of the battery cell is reduced, and the rate performance of the battery cell is improved.

[0044] According to some embodiments of the present application, the electrode assembly further includes a separator, and the porosity of the separator is 20% - 70%. Thus, the transmission efficiency of lithium ions is improved, and the rate performance of the battery cell is improved.

[0045] According to some embodiments of the present application, the porosity of the separator is 35% - 60%. Thus, the transmission efficiency of lithium ions is improved, and the rate performance of the battery cell is improved.

[0046] According to some embodiments of the present application, the separator includes: a base film; a first functional layer located on at least one side of the base film, and the first functional layer includes a first inorganic substance; a second functional layer located on the side of the first functional layer away from the base film, and the second functional layer includes a second inorganic substance and a non-fluoropolymer. Thus, the heat resistance of the separator is improved, and the safety of the battery cell is improved.

[0047] According to some embodiments of the present application, the non-fluoropolymer includes an acrylate copolymer. Thus, the adhesiveness of the non-fluoropolymer is improved, and the risk of the second functional layer peeling off is reduced.

[0048] According to some embodiments of the present application, the first inorganic substance and the second inorganic substance each independently include one or more of silicon oxide, aluminum oxide, boehmite, barium sulfate, calcium oxide, titanium oxide, zinc oxide, magnesium oxide, zirconium oxide, and tin oxide. Thus, the heat resistance of the separator is improved, and the safety of the battery cell is improved.

[0049] According to some embodiments of the present application, the thickness of the base film is 4 μm - 12 μm. Thus, while reducing the short circuit between the positive and negative electrodes, the volume occupied by the separator in the battery cell is reduced, and the energy density of the battery cell is increased.

[0050] According to some embodiments of the present application, the thickness of the base film is 5 μm - 9 μm. The volume occupied by the separator in the battery cell is reduced, and the energy density of the battery cell is increased.

[0051] According to some embodiments of the present application, the battery cell includes a housing and a cover assembly. The cover assembly is disposed at at least one end of the housing. The housing and the cover assembly define a receiving cavity. The electrode assembly is disposed in the receiving cavity. The thickness of the housing on the large surface of the battery cell is 0.1 mm - 0.5 mm. Thus, the energy density of the battery cell is increased.

[0052] According to some embodiments of the present application, the thickness of the housing on the large surface is 0.2 mm - 0.35 mm. Thus, the energy density of the battery cell is increased.

[0053] According to some embodiments of the present application, the cover assembly includes a first cover assembly and a second cover assembly. The first cover assembly and the second cover assembly are disposed at two ends of the housing in the length direction or the width direction. The first cover assembly includes a first cover and a first electrode terminal. The second cover assembly includes a second cover and a second electrode terminal. The polarities of the first electrode terminal and the second electrode terminal are opposite. Thus, during charging, the temperature rise of the battery cell is reduced, and further the impedance of the battery cell is reduced.

[0054] According to some embodiments of the present application, the minimum cross-sectional area of the first electrode terminal and / or the second electrode terminal is S, and it satisfies 150 mm 2 ≤ S ≤ 1000 mm 2 . Thus, the overcurrent capacity of the battery cell is increased.

[0055] The second aspect of the present application provides a battery device, including the battery cell provided by the first aspect of the present application. The battery device is one or more of a battery module, a battery pack, and an energy storage device.

[0056] The third aspect of the present application provides an electrical device, including the battery cell provided by the first aspect of the present application or the battery device provided by the second aspect of the present application. The battery cell or the battery device provides electrical energy for the electrical device.

[0057] The additional aspects and advantages of the present application will be partially given in the following description, partially become apparent from the following description, or be understood through the practice of the present application. Description of the Drawings

[0058] Upon reading the following detailed description of the preferred embodiments, various other advantages and benefits will become clear to those of ordinary skill in the art. The drawings are only for the purpose of showing the preferred embodiments and are not considered to be a limitation of the present application. Also, in all the drawings, the same reference numerals are used to represent the same components. In the drawings: Figure 1 is a schematic diagram of the dimensions of the positive electrode active material layer and the negative electrode active material layer of an embodiment of the present application.

[0059] Figure 2 is a schematic structural diagram of a positive electrode plate of an embodiment of the present application.

[0060] Figure 3 is a schematic structural diagram of a positive electrode plate of another embodiment of the present application.

[0061] Figure 4 is a schematic structural diagram of a positive electrode plate of another embodiment of the present application.

[0062] Figure 5 is a schematic structural diagram of a positive electrode plate of another embodiment of the present application.

[0063] Figure 6 is a schematic structural diagram of a negative electrode plate of an embodiment of the present application.

[0064] Figure 7 is a schematic structural diagram of a negative electrode plate of another embodiment of the present application.

[0065] Figure 8 is a schematic structural diagram of a negative electrode plate of another embodiment of the present application.

[0066] Figure 9 is a schematic structural diagram of a negative electrode plate of another embodiment of the present application.

[0067] Figure 10 is a schematic structural diagram of a separator of an embodiment of the present application.

[0068] Figure 11 is a schematic structural diagram of a housing of an embodiment of the present application.

[0069] Figure 12 is a schematic structural diagram of a battery cell of an embodiment of the present application.

[0070] Figure 13 is a schematic structural diagram of an electrical device of an embodiment of the present application.

[0071] Description of reference numerals: 1 Battery cell; 11 Housing; 111 Large-surface housing; 121 Positive electrode plate; 1210 Positive electrode tab; 1212 Positive electrode active material layer; 122 Negative electrode plate; 1220 Negative electrode tab; 1222 Negative electrode active material layer; 123 Separator; 1231 Base film; 1232 First functional layer; 1233 Second functional layer; 131 First electrode terminal; 132 Second electrode terminal; 133 Third electrode terminal; 134 Fourth electrode terminal. Detailed implementation manners

[0072] The embodiments of the technical solutions of the present application will be described in detail below. The following embodiments are only used to illustrate the technical solutions of the present application more clearly, and therefore are only examples and cannot be used to limit the protection scope of the present application.

[0073] Referring to "embodiments" herein means that the specific features, structures or characteristics described in connection with the embodiments can be included in at least one embodiment of the present application. The phrase appears in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment mutually exclusive with other embodiments. Those skilled in the art explicitly and implicitly understand that the embodiments described herein can be combined with other embodiments.

[0074] If there is no special description, all implementation manners and optional implementation manners of the present application can be combined with each other to form a new technical solution.

[0075] If there is no special description, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0076] If there is no special description, all steps of the present application can be carried out in sequence or randomly, and preferably in sequence. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) carried out in sequence, or may include steps (b) and (a) carried out in sequence. For example, it is mentioned that the method may further include step (c), indicating that step (c) can be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0077] Currently, from the perspective of the development of the market situation, the application of batteries is becoming more and more extensive. Batteries are not only used in energy storage power systems such as hydropower, thermal power, wind power and solar power plants, but also widely used in electric vehicles such as electric bicycles, electric motorcycles and electric vehicles, as well as in multiple fields such as military equipment and aerospace. With the continuous expansion of the battery application field, the market demand is also continuously increasing.

[0078] During the cycling process of a lithium iron phosphate system battery cell, the HF generated will corrode the solid electrolyte interface (SEI) film on the surface of the negative electrode, reducing the cycle life of the battery. By adding a relatively large amount of carbonate additives to the electrolyte, the stability of the SEI film can be improved, and the cycle life of the battery cell can be increased. However, excessive carbonate additives will increase the viscosity of the electrolyte, affect the transport of lithium ions, and reduce the fast charging performance of the battery cell.

[0079] In a first aspect of the present application, a battery cell is provided. The battery cell includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode tab, where the positive electrode tab includes a positive electrode current collector and a positive electrode active material layer provided on at least one side of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes a lithium-containing phosphate; the electrolyte includes: a first solvent, the first solvent includes one or two of ethylene carbonate and propylene carbonate. Based on the total mass of the electrolyte, the mass ratio of the first solvent is 20%-40%; a first additive, the first additive includes one or two of vinylene carbonate and ethylene carbonate derivatives. Based on the total mass of the electrolyte, the mass ratio of the carbonate additive is 1%-8%. The ethylene carbonate derivative includes a compound represented by formula II: Formula II, wherein, R 1 , R 2 , R 3 , R 4 each independently includes any one of a hydrogen atom, a halogen atom, a C1-C5 alkyl group, and a C1-C5 haloalkyl group, and R 1 , R 2 , R 3 , R 4 are not simultaneously hydrogen atoms; a second additive, the second additive includes a compound represented by formula I: R 1 -COOLi Formula I, wherein, R 1 includes any one of a hydrogen atom, a halogen atom, a C1-C5 alkyl group, and a C1-C5 haloalkyl group. Based on the total mass of the electrolyte, the mass ratio of the second additive in the electrolyte is 0.1%-4%.

[0080] In this application, after disassembling the battery cell to obtain the electrolyte, reference can be made to GB / T 9722-2023 General Rules for Chemical Reagents - Gas Chromatography to qualitatively and quantitatively analyze the first solvent, the first additive, and the second additive in the electrolyte by gas chromatography.

[0081] As an example, based on the total mass of the electrolyte, the mass percentage of the first solvent can be 20%, 25%, 30%, 35%, 40%, etc., or can be a range composed of any of the above values.

[0082] As an example, based on the total mass of the electrolyte, the mass percentage of the carbonate additive can be 1%, 3%, 5%, 7%, 8%, etc., or can be a range composed of any of the above values.

[0083] As an example, based on the total mass of the electrolyte, the mass percentage of the second additive in the electrolyte can be 0.1%, 0.5%, 1%, 2%, 3%, 4%, etc., or can be a range composed of any of the above values.

[0084] In this application, the term "halogen atom" includes one or more of fluorine atom, chlorine atom, and iodine atom.

[0085] In this context, the term "C1-C5 alkyl" refers to a straight-chain or branched-chain hydrocarbon chain group consisting only of carbon and hydrogen atoms, with no unsaturation in the group, having from one to five carbon atoms, and attached to the rest of the molecule by a single bond. As an example, it includes but is not limited to methyl, ethyl, propyl, isopropyl, 2-methyl-1-propyl, 2-methyl-2-propyl, 2-methyl-1-butyl, 3-methyl-1-butyl, 2-methyl-3-butyl, 2,2-dimethyl-1-propyl, 2-methyl-1-pentyl, butyl, isobutyl, tert-butyl, pentyl, isopentyl, neopentyl.

[0086] In this context, the term "C1-C5 haloalkyl" refers to a C1-C5 alkyl in which at least one hydrogen atom is replaced by a halogen atom. As an example, it includes but is not limited to: -CF 3 , -CF 2 CH 2 , -CF 2 CH 2 CH 3 , -CF 2 CF 2 CH 2 CH 3 , -CF 2 CH 2 CH 2 CH 2 CH 3 .

[0087] Additives refer to components with relatively low contents in the electrolyte, generally with a mass fraction in the electrolyte not exceeding 10%. They are characterized by strong pertinence and small dosages. Without changing the production process, they can significantly optimize a certain aspect of the battery's performance.

[0088] For the battery cell proposed in this application, the electrolyte includes a first solvent. The first solvent has good solubility for the electrolyte salt in the electrolyte, and has a relatively high dielectric constant and excellent chemical stability, which can improve the conduction rate of lithium ions, reduce the DC impedance of the battery, and improve the cycle stability of the battery cell. At the same time, by controlling the content of the first solvent, while improving the conduction rate of lithium ions, the viscosity of the electrolyte is reduced, and the DC impedance of the battery cell is reduced. In addition, since there is trace crystalline water in the battery that cannot be completely removed through the process, during the use of the battery, the common lithium salt (such as lithium hexafluorophosphate, LiPF 6 6) in the electrolyte will hydrolyze to produce HF, which will corrode the SEI film. In this application, by adding a second additive R 1 -COOLi to the electrolyte, the second additive has a stronger binding energy with H 2 2O and can preferentially combine with H 2 2O to form R 1 -COO - -H 2 2O with a higher energy barrier, thereby reducing the hydrolysis of LiPF 6 6 and the generation of HF, avoiding the consumption of the first additive caused by the corrosion of the SEI film by a large amount of HF during the cycle of the battery cell, reducing the consumption rate of the first additive, so that the usage amount of the first additive can be reduced to 1%-8%, avoiding the influence of excessive first additive on the viscosity of the electrolyte, being beneficial to improving the transmission speed of lithium ions in the electrolyte, reducing the DC impedance of the battery, and improving the fast charging performance of the battery. And the R 1 -COOLi additive has a high donor number, and its anion has a strong coordination ability with Li, which can preferentially occupy the inner layer of the solvation shell, thereby reducing the desolvation energy barrier of Li + +, and improving the fast charging performance of the electrolyte in a system containing a large amount of ethylene carbonate and / or propylene carbonate. By controlling the content of the second additive, while reducing the generation of HF, it can also avoid the corrosion phenomenon brought by excessive second additive to the current collector, improve the cycle stability of the battery cell, improve the film formation impedance deteriorated due to the too thick SEI film, reduce the DC impedance of the battery, and improve the kinetic performance of the battery cell. In addition, the positive electrode active material includes a lithium-containing phosphate with an olivine structure, which has excellent structural stability and can improve the cycle performance of the battery cell.

[0089] In the present application, vinylene carbonate and / or vinyl carbonate derivatives are added to the electrolyte. Vinylene carbonate and vinyl carbonate derivatives can participate in the formation of SEI film on the negative electrode side in priority to other components in the electrolyte, and the film formed by vinylene carbonate and vinyl carbonate derivatives has a high content of organic matter, which is beneficial to improve the overall flexibility of the SEI film, improve the stability of the SEI film and the negative electrode interface during the cycle, reduce the reaction between the negative electrode active material and the electrolyte, reduce the consumption of lithium ions, and improve the cycle performance and storage performance of the battery cell.

[0090] In summary, the present application can achieve a balance between fast charging performance and cycle performance by collaboratively controlling the type and content of the first solvent, the type and content of the first additive, and the type and content of the second additive within an appropriate range.

[0091] According to some embodiments of the present application, based on the total mass of the electrolyte, the mass proportion of the second additive may be 0.5%-2%. For example, it may be 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, 1.7%, 1.9%, 2%, etc., or may be a range consisting of any of the above values.

[0092] When the mass content of the second additive is within an appropriate range, it can combine with water, reduce HF generation, improve the cycle performance of the battery, and at the same time reduce the viscosity of the electrolyte, while taking into account the fast charging performance of the battery.

[0093] According to some embodiments of the present application, the second additive includes one or more of lithium acetate, lithium difluoroacetate, and lithium trifluoroacetate. 6 The hydrolysis of and the generation of HF reduce the corrosion of the SEI film.

[0094] According to some embodiments of the present application, the second additive includes lithium trifluoroacetate. Therefore, when polyfluorinated lithium trifluoroacetate is selected as the second additive, the acidity of lithium trifluoroacetate is relatively weak, which can reduce the corrosion to the aluminum foil.

[0095] According to some embodiments of the present application, the electrolyte further includes a second solvent, and the second solvent includes one or both of a carboxylate solvent and a linear carbonate solvent.

[0096] The carboxylic acid ester solvent and the chain carbonate solvent have low viscosity, thereby improving the conductivity of the electrolyte solution.

[0097] According to some embodiments of the present application, based on the total mass of the electrolyte, the mass proportion of the second solvent may be 45%-65%. For example, it may be 45%, 50%, 55%, 60%, 65%, etc., or may be a range consisting of any of the above values. Thus, the conductivity of the electrolyte is improved.

[0098] According to some embodiments of the present application, the carboxylic ester solvent includes a compound represented by Formula III: Formula III wherein R 5 includes any one of a hydrogen atom, a halogen atom, an alkyl group having 1 to 5 carbon atoms, and a halogenated alkyl group having 1 to 5 carbon atoms, and R 6 includes any one of an alkyl group having 1 to 5 carbon atoms and a halogenated alkyl group having 1 to 5 carbon atoms. Thus, the carboxylic ester solvents of the above types have a small molecular weight, low viscosity, can improve the ionic conductivity of the electrolyte, and improve the rate performance of the battery cell.

[0099] According to some embodiments of the present application, the carboxylic ester solvent includes one or more of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, and ethyl butyrate. Thus, the carboxylic ester solvents of the above types have a small molecular weight, low viscosity, can improve the ionic conductivity of the electrolyte, and improve the rate performance of the battery cell.

[0100] According to some embodiments of the present application, the chain carbonate solvent includes one or more of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. Thus, the viscosity of the electrolyte is reduced, and the ionic conductivity of the electrolyte is improved. When the electrolyte simultaneously includes cyclic carbonates (ethylene carbonate, propylene carbonate) and chain carbonates, the chain carbonates have low viscosity and high ionic conductivity, and the cyclic carbonates have high dielectric constant and high solubility of lithium salts, which can improve the comprehensive performance of the electrolyte.

[0101] According to some embodiments of the present application, when the second solvent includes a chain carbonate solvent, based on the total mass of the electrolyte, the mass ratio of the first additive may be 1% - 3%. For example, it may be 1%, 1.5%, 2%, 2.5%, 3%, etc., or may be a range composed of any of the above values. Compared with the carboxylic ester solvent, the activity of the chain carbonate solvent is reduced, and there are fewer side reactions at the negative electrode interface. A relatively small amount of the first additive participates in film formation, which can make the battery cell have a good cycle life and prevent excessive addition of the first additive from increasing the film formation impedance.

[0102] According to some embodiments of the present application, the second solvent includes a carboxylic acid ester solvent and a linear carbonate solvent. Based on the total mass of the electrolyte, the mass proportion of the carboxylic acid ester solvent is 8% - 60%, and the mass proportion of the first additive is 3% - 8%. For example, it can be 3%, 4%, 5%, 6%, 7%, 8%, etc., or it can be a range composed of any of the above values. Thus, when the electrolyte contains both a carboxylic acid ester solvent and a linear carbonate solvent, the activity of the electrolyte is relatively strong, and the side reaction with the negative electrode interface is relatively strong. Therefore, more of the first additive needs to be added to form a more stable SEI film, maintain the interface, and improve the cycle life of the battery cell.

[0103] In the present application, the testing of the type and content of the second solvent can be carried out with reference to the testing methods of the type and content of the aforementioned first solvent, first additive, and second additive.

[0104] According to some embodiments of the present application, the electrolyte further includes a lithium salt, and the lithium salt may include one or two of lithium fluorosulfonylimide salt and lithium hexafluorophosphate. Thus, the ionic conductivity of the electrolyte is improved.

[0105] When the electrolyte contains both lithium fluorosulfonylimide salt and lithium hexafluorophosphate, the ion transference number of lithium fluorosulfonylimide is relatively large, which can improve the migration rate of lithium ions. The stability of lithium hexafluorophosphate is relatively good. The combination of the two can improve the stability and ionic conductivity of the electrolyte.

[0106] According to some embodiments of the present application, based on the total mass of the electrolyte, the mass proportion of the lithium salt is 10% - 18%. For example, it can be 10%, 12%, 14%, 16%, 18%, etc., or it can be a range composed of any of the above values. Thus, while improving the ionic conductivity of the electrolyte, the viscosity of the electrolyte is reduced.

[0107] In the present application, the testing of the content of lithium fluorosulfonylimide salt and lithium hexafluorophosphate can refer to the standard JY / T 020 - 2002 "General Rules for Ion Chromatography Analysis Method". For example, newly prepared electrolyte can be taken as a sample, or the free electrolyte of a fresh battery can be taken as a sample. Or, the battery cell that has been fully discharged (discharged to the discharge cut-off voltage so that the charged state of the battery cell is approximately 0% SOC) can be disassembled in reverse, and the free electrolyte obtained from the battery cell can be taken as a sample. The ion chromatography analysis method is used for detection, the inorganic ion chromatogram is tested, the corresponding inorganic substances are compared according to the position of the chromatographic peak, and the percentage of the content of the corresponding inorganic ions is calculated according to the peak area. Then, the ratio of the mass proportion of lithium fluorosulfonylimide to the mass proportion of lithium hexafluorophosphate is calculated.

[0108] According to some embodiments of the present application, based on the total mass of the electrolyte, the mass proportion of the lithium fluorosulfonylimide salt can be 4% - 6%. For example, it can be 4%, 4.5%, 5%, 5.5%, 6%, etc., or it can be a range composed of any of the above values. Thereby, the migration rate of lithium ions is increased.

[0109] According to some embodiments of the present application, the lithium fluorosulfonylimide salt includes one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium perfluorobutanesulfonylimide. Thereby, the migration rate of lithium ions is increased.

[0110] According to some embodiments of the present application, the electrolyte further includes a third additive, and the third additive includes one or more of a sulfur-containing additive and a lithium salt additive. Thereby, the cycle performance and fast charging performance of the battery cell are improved.

[0111] According to some embodiments of the present application, the sulfur-containing additive includes one or more of ethylene sulfate, bis(ethylene sulfate), 1,3 - propane sultone, butene sulfite, ethylene sulfite, and methylene methanedisulfonate. Thereby, the impedance of the battery cell is reduced, and the fast charging performance of the battery cell is improved.

[0112] According to some embodiments of the present application, based on the total mass of the electrolyte, the mass proportion of the sulfur-containing additive can be 0% - 2%. For example, it can be 0.5%, 1%, 1.5%, 2%, etc., or it can be a range composed of any of the above values. Thereby, while reducing the impedance of the battery cell, the risk of the battery cell being oxidized at a high potential to generate sulfur-containing free radicals is reduced, and further, the decomposition of the solvent caused by the sulfur-containing free radicals is reduced, and the gas generation of the battery cell is reduced. According to some embodiments of the present application, the mass proportion of the sulfur-containing additive can be 0.5% - 2%.

[0113] According to some embodiments of the present application, the lithium salt additive includes one or more of lithium difluorophosphate, lithium difluoro(oxalato)borate, lithium tetrafluoroborate, and lithium bis(oxalato)borate. Thereby, the gas generation of the battery cell under high temperature conditions is reduced.

[0114] According to some embodiments of the present application, based on the total mass of the electrolyte, the mass proportion of the lithium salt additive can be 0% - 1%. For example, it can be 0.2%, 0.4%, 0.6%, 0.8%, 1%, etc., or it can be a range composed of any of the above values. Thereby, while reducing the gas generation of the battery cell, the content of inorganic components in the SEI film is reduced, and the film formation impedance is reduced. According to some embodiments of the present application, the mass proportion of the lithium salt additive can be 0.2% - 1%.

[0115] It should be noted that since the additives in the electrolyte are consumed during formation and charge-discharge cycles, generating relevant components in the SEI film and / or CEI film, when the content of sulfur-containing additives and lithium salt additives is tested by gas chromatography after disassembling the battery cell to obtain the electrolyte, the content may be 0.

[0116] Specifically, taking the case where the mass content of sulfur-containing additives is 0 as an example, it may be that the freshly prepared electrolyte does not contain sulfur-containing additives, or the electrolyte obtained after disassembling the battery cell does not contain sulfur-containing additives. This situation may be that the freshly prepared electrolyte does not contain sulfur-containing additives, or a small amount of sulfur-containing additives are added, but they participate in the film-forming reaction of the SEI film during the formation of the battery cell, resulting in a mass content of 0 for the sulfur-containing additives during the detection. Optionally, the freshly prepared electrolyte includes sulfur-containing additives.

[0117] Furthermore, for adding certain substances, such as additives, to the electrolyte, due to the characteristic that the additives play a role by participating in the film formation on the surface of the active material, the content of additives in the electrolyte of the battery cell is related to formation, different battery life cycles, or different battery storage states. Therefore, there may be a difference in the content of additives between the freshly prepared electrolyte and the electrolyte obtained by reverse-disassembling the battery cell. However, those skilled in the art can know the approximate range of the content of relevant substances in the corresponding freshly prepared electrolyte according to the performance expression level (such as the number of cycles) and residual content of the battery cell. Similarly, those skilled in the art can also know the approximate range of the content of the non-freshly prepared (i.e., reverse) electrolyte according to the content of the freshly prepared additives, based on the performance requirements and storage environment of the battery cell.

[0118] Therefore, the additive content mentioned in the technical solution of this application can be the content of additives actively added to the freshly prepared electrolyte, or the content of residual additives detected by reverse according to the actual battery state.

[0119] In this application, the types and contents of sulfur-containing additives and the types and contents of lithium salt additives can be tested with reference to the testing methods for the types and contents of the aforementioned first solvent, first additive, and second additive.

[0120] In this application, additives refer to components with a relatively low content in the electrolyte, generally with a mass ratio in the electrolyte not exceeding 10%. They have the characteristics of strong pertinence and small dosage, and can significantly optimize a certain aspect of the battery performance without changing the production process.

[0121] According to some embodiments of the present application, the lithium-containing phosphate includes: a matrix; a first coating material located on at least a part of the surface of the matrix, and the first coating material contains carbon elements. Thus, a good conductive network is formed between the lithium-containing phosphate particles, improving the electronic conductivity of the lithium-containing phosphate.

[0122] According to some embodiments of the present application, based on the total mass of the lithium-containing phosphate, the mass percentage of the carbon element is 0.8% - 2.3%. For example, it can be 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.3%, etc., or it can be a range composed of any of the above values. Thus, while improving the electronic conductivity of the lithium-containing phosphate, the influence on lithium ion transport is reduced, the loading of the lithium-containing phosphate on the positive electrode sheet is increased, and the energy density of the battery cell is improved.

[0123] Generally, infrared absorption is used to measure the carbon content in the material, such as an infrared carbon-sulfur instrument, or the method of fixed carbon determination, and the latter can refer to the content on pages 3 - 4 of the national standard GB / T 3521-2008 (Methods for Chemical Analysis of Graphite).

[0124] According to some embodiments of the present application, the first coating material includes the compound shown in Formula IV: Li 3-d1 Fe 2-d1 M1 d1 (PO m1 ) n1 Formula IV, where 0 ≤ d1 ≤ 1, 3 ≤ m1 ≤ 5, 2 ≤ n1 ≤ 4, and M1 includes one or more of Ti, Zr, Hf, Ge, and Sn. Thus, the ionic conductivity and specific capacity of the positive electrode active material are improved, and the fast charging performance and energy density of the battery cell are improved.

[0125] The first coating layer includes Li 3-d1 Fe 2-d1 M1 d1 (PO m1 ) n1 , which has excellent ionic conductivity, and together with the carbon element with excellent conductivity in the coating layer, improves the conductivity and ionic conductivity of the material, which is beneficial to improving the fast charging performance of the battery.

[0126] According to some embodiments of the present application, the matrix includes the compound shown in Formula V: Li x1 A y1 Me a1 M2 b1 P 1-c1 X c1 Y z1 Formula V, Among them, 0.5 ≤ x 1 ≤ 1.3, 0 ≤ y 1 ≤ 1.3, 0.9 ≤ x 1 + y 1 ≤ 1.3; 0.9 ≤ a 1 ≤ 1.5, 0 ≤ b 1 ≤ 0.5, 0.9 ≤ a 1 + b 1 ≤ 1.5; 0 ≤ c 1 ≤ 0.5; 3 ≤ z 1 ≤ 5; Among them, A includes one or more of Na, K, and Mg; Me includes one or more of Mn, Fe, Co, and Ni; M2 includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X includes one or more of Cl, C, and N; Y includes one or more of O and F. Thus, the cycle performance and safety of the battery cell are improved.

[0127] As an example, x 1 can be 0.5, 0.7, 0.9, 1.1, 1.3, etc., or can be a range composed of any of the above values.

[0128] It should be noted that due to processes such as formation and cycling of the battery cell, lithium ions will be consumed, so there will be a situation where the lithium element content x in the positive electrode active material measured 1 is less than 1. At the same time, if a lithium supplement agent is used in the positive electrode plate and the negative electrode plate, after the battery undergoes processes such as formation and cycling, there will be a situation where the lithium element content x in the positive electrode active material measured 1 is greater than 1.

[0129] As an example, y 1 can be 0, 0.3, 0.6, 0.9, 1.3, etc., or can be a range composed of any of the above values.

[0130] As an example, a 1 can be 0.9, 1.1, 1.3, 1.5, etc., or can be a range composed of any of the above values.

[0131] As an example, b 1 can be 0, 0.2, 0.4, 0.5, etc., or can be a range composed of any of the above values.

[0132] As an example, c 1 can be 0, 0.2, 0.4, 0.5, etc., or can be a range composed of any of the above values.

[0133] As an example, z 1 can be 3, 4, 5, etc., or can be a range composed of any of the above values.

[0134] According to some embodiments of the present application, the matrix includes one or more of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium nickel phosphate, and lithium cobalt phosphate. Thereby, the cycle performance and safety of the battery cell are improved.

[0135] According to some embodiments of the present application, when the battery cell is in a 0% state of charge, the tap density of the positive electrode plate is 2.46 g / cm 3 -2.8 g / cm 3 . For example, it can be 2.46 g / cm 3 , 2.5 g / cm 3 , 2.6 g / cm 3 , 2.7 g / cm 3 , 2.8 g / cm 3 etc., or can be a range composed of any of the above values. Thereby, the energy density of the battery cell is improved.

[0136] The present application provides a method for testing the tap density of a positive electrode plate: charge at a constant current of 1 / 3C to 3.65V, charge at a constant voltage of 3.65V to 0.05C, place the battery cell at 25°C, let it stand for 2h, and then discharge at a rate of 0.33C to 2.0V. Disassemble the battery cell to obtain the positive electrode plate. For example, take a single-sided coated positive electrode plate (if it is a double-sided coated plate, the positive electrode active material layer on one side can be wiped off first), punch it into small round pieces with an area of S 1 , weigh it, and record it as M 1 , and measure its thickness H 1 . Then wipe off the positive electrode active material layer of the above-mentioned weighed positive electrode plate, weigh the positive electrode current collector, and record it as M 0 , and measure its thickness H 0 . The single-sided coating weight of the positive electrode active material layer = (M 1 - M 0 ) / S 1 , the thickness of the positive electrode active material layer = H 1 - H 0 , and the tap density of the positive electrode active material layer = the single-sided coating weight of the positive electrode active material layer / the thickness of the positive electrode active material layer.

[0137] According to some embodiments of the present application, the single-sided coating weight of the positive electrode active material layer is 200 mg / 1540.25 mm 2 -400 mg / 1540.25 mm 2For example, it can be 200 mg / 1540.25 mm 2 、250 mg / 1540.25 mm 2 、300 mg / 1540.25 mm 2 、340 mg / 1540.25 mm 2 、370 mg / 1540.25 mm 2 、400 mg / 1540.25 mm 2 etc., or it can be a range composed of any of the above values. Thereby, the energy density of the battery cell is increased.

[0138] The present application provides a method for testing the coating weight of the positive electrode active material layer: disassemble the positive electrode plate from the battery cell. For example, take the single-sided coated positive electrode plate (if it is a double-sided coated plate, the positive electrode active material layer on one side can be wiped off first), and punch it into small circular pieces with an area of S 1 . Weigh it and record it as M 1 . Then wipe off the positive electrode active material layer of the above-mentioned weighed positive electrode plate, and weigh the weight of the positive electrode current collector, and record it as M 0 . The single-sided coating weight of the positive electrode active material layer = (M 1 - M 0 ) / S 1 .

[0139] According to some embodiments of the present application, the electrode assembly further includes a negative electrode plate, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer provided on at least one side of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes one or two of a carbon-based material and a silicon-based material. Thereby, the energy density and cycle performance of the battery cell are improved.

[0140] According to some embodiments of the present application, the carbon-based material includes graphite. Thereby, the cycle performance of the battery cell is improved.

[0141] According to some embodiments of the present application, the graphite is secondary particles formed by aggregation of primary particles, and at least part of the surface of the secondary particles has a second coating material, and the second coating material includes amorphous carbon.

[0142] Secondary particles refer to particles formed by aggregation of two or more primary particles.

[0143] In this article, amorphous carbon refers to a transition carbon material with a very low degree of graphitization crystallization, approximately amorphous form (or no fixed shape and periodic structural rules). In the present application, amorphous carbon refers to the product after carbonization treatment of an organic carbon source, which has more end faces and defects and more lithium ion sites.

[0144] Secondary particles can enhance the migration rate of lithium ions, improve the transport performance of lithium ions, facilitate the insertion and extraction of lithium ions, and contribute to enhancing the ionic conductivity of the material. The second coating material includes amorphous carbon, which can improve the electrical conductivity of the composite graphite particles. The secondary particles in the core and the coating layer of amorphous carbon jointly improve the electron-conducting and ion-conducting properties of the material, helping to enhance the fast-charging performance of the battery cell.

[0145] According to some embodiments of the present application, based on the total mass of the graphite, the mass ratio of the second coating material is 2% - 5%. For example, it can be 2%, 3%, 4%, 5%, etc., or it can be a range composed of any of the above values. Controlling the mass content of the second coating material within an appropriate range can improve the electrical conductivity of the material and enhance the fast-charging performance of the battery.

[0146] According to some embodiments of the present application, the volume-average particle size Dv50 of the graphite is 8.5 μm - 14.8 μm. For example, it can be 8.5 μm, 9.5 μm, 10.5 μm, 11.5 μm, 12.5 μm, 13.5 μm, 14.8 μm, etc., or it can be a range composed of any of the above values. Thus, the volume-average particle size of the graphite is relatively small, which can shorten the solid-phase migration path of lithium ions and improve the fast-charging ability of the battery cell. At the same time, by making the volume-average particle size within the above range, side reactions between the graphite anode and the electrolyte can also be reduced.

[0147] In the present application, Dv50 refers to the particle size corresponding to when the cumulative volume distribution percentage reaches 50%. For example, referring to the standard GB / T 19077 - 2016 / ISO 13320:2009, it is measured using a laser particle size analyzer (Malvern Master Size 2000). The specific test process is as follows: Discharge the battery cell to 0% SOC, then disassemble it to take the negative electrode sheet, scrape a certain amount of powder on the electrode sheet with a blade, and then use deionized water to wash it repeatedly by shaking 5 - 10 times. After drying, sinter it in a tube furnace at 400 °C for 2 h. After sintering, take an appropriate amount of the sample to be measured (the sample concentration should ensure a light transmittance of 8% - 12%), add deionized water, and disperse it ultrasonically to ensure that the sample is completely dispersed. Then, measure the sample with reference to the standard GB / T19077 - 2016 / ISO 13320:2009.

[0148] According to some embodiments of the present application, the negative electrode active material includes a silicon-based material. Based on the total mass of the negative electrode active material layer, the mass ratio of silicon element is 0.3% - 5%. For example, it can be 0.3%, 1%, 3%, 5%, etc., or it can be a range composed of any of the above values. Thereby, the energy density of the battery cell is increased.

[0149] The qualitative and quantitative determination of each substance or element in this application can be detected by suitable equipment and methods known to those skilled in the art. Relevant detection methods can refer to domestic and foreign detection standards, domestic and foreign enterprise standards, etc. And those skilled in the art can also adaptively change some detection steps / instrument parameters, etc. from the perspective of detection accuracy to obtain more accurate detection results. One detection method can be used for qualitative or quantitative determination, or several detection methods can be used in combination for qualitative or quantitative determination.

[0150] For example, the mass content of silicon element in the negative electrode active material layer has the meaning well-known in the art and can be detected by equipment and methods well-known in the art. For example, the negative electrode sheet is placed in a solvent such as water for soaking to separate the negative electrode active material from the negative electrode current collector, and the substances in the negative electrode active material layer are obtained by suction filtration and used as test samples. The test samples are analyzed by an inductively coupled plasma - emission spectrometer of model ICAP7400 from Thermo Fisher Scientific Company in the United States, and referring to the standard of GB / T30902 - 2014, the content of silicon element can be obtained.

[0151] According to some embodiments of the present application, the single-sided coating weight of the negative electrode active material layer is 90mg / 1540.25mm 2 -185mg / 1540.25mm 2 . For example, it can be 90mg / 1540.25mm 2 , 110mg / 1540.25mm 2 , 125mg / 1540.25mm 2 , 140mg / 1540.25mm 2 , 185mg / 1540.25mm 2 etc., thereby improving the energy density of the battery cell.

[0152] The present application provides a method for testing the coating weight of the negative electrode active material layer: The negative electrode sheet is disassembled from the battery cell. For example, a single-sided coated negative electrode sheet is taken (if it is a double-sided coated sheet, the negative electrode active material layer on one side can be wiped off first), and it is punched into small round pieces with an area of S 2 , and its weight is measured and recorded as M 3 . Then, the negative electrode active material layer of the above-mentioned weighed negative electrode sheet is wiped off, and the weight of the negative electrode current collector is measured and recorded as M 2 . The single-sided coating weight of the negative electrode active material layer = (M 3 - M 2 ) / S 2 .

[0153] According to some embodiments of the present application, along the length direction of the battery cell, the size of the negative electrode active material layer is larger than that of the positive electrode active material layer, and the difference between the size of the negative electrode active material layer and the size of the positive electrode active material layer is OH 1 ; along the width direction of the battery cell, the size of the negative electrode active material layer is larger than that of the positive electrode active material layer, and the difference between the size of the negative electrode active material layer and the size of the positive electrode active material layer is OH 2 , where OH 1 is greater than or equal to OH 2 .

[0154] During fast charging, the current flowing through the electrode tab side of the electrode is large, the temperature is higher, the lithium ion migration rate is faster than other parts, and lithium deposition is likely to occur. By making the size of the negative electrode active material layer larger than that of the positive electrode active material layer, more negative electrode active material layers can receive lithium ions, improving lithium deposition. And since the lithium ion diffusion path is longer in the length direction of the battery cell, by making OH 1 greater than or equal to OH 2 , more negative electrode active material layers can receive lithium ions in the length direction, reducing the risk of lithium ion precipitation at the edge.

[0155] Specifically, referring to Figure 1 , along the length direction of the battery cell, the size of the positive electrode active material layer 1212 is OH 11 , the size of the negative electrode active material layer 1222 is OH 21 , and the difference between the size of the negative electrode active material layer 1222 and the size of the positive electrode active material layer 1212 is OH 1 =OH 21 -OH 11 .

[0156] Referring to Figure 1 , along the width direction of the battery cell, the size of the positive electrode active material layer 1212 is OH 12 , the size of the negative electrode active material layer 1222 is OH 22 , and the difference between the size of the negative electrode active material layer 1222 and the size of the positive electrode active material layer 1212 is OH 2 =OH 22 -OH 12 .

[0157] According to some embodiments of the present application, 1 mm ≤ OH 1 ≤ 4 mm. For example, it can be 1 mm, 2 mm, 3 mm, 4 mm, etc., or it can be a range composed of any of the above values.

[0158] According to some embodiments of the present application, 1 mm ≤ OH 2 ≤ 3 mm. For example, it can be 1 mm, 2 mm, 3 mm, etc., or it can be a range composed of any of the above values. Thus, while reducing lithium deposition on the negative electrode, the volumetric energy density of the battery cell is taken into account.

[0159] According to some embodiments of the present application, a positive electrode tab is provided on the positive electrode plate, and a negative electrode tab is provided on the negative electrode plate. The positive electrode tab extends along the length direction or the width direction of the positive electrode plate; and / or the negative electrode tab extends along the length direction or the width direction of the negative electrode plate. Thus, the current transmission efficiency is improved, the resistance of the battery cell is reduced, and the rate performance of the battery cell is improved.

[0160] Referring to Figure 2 , only one positive electrode tab 1210 extends along the length direction of the positive electrode plate 121. Referring to Figure 3 , positive electrode tabs 1210 extend from both ends along the length direction of the positive electrode plate 121.

[0161] Referring to Figure 4 , only one positive electrode tab 1210 extends along the width direction of the positive electrode plate 121. Referring to Figure 5 , positive electrode tabs 1210 extend from both ends along the width direction of the positive electrode plate 121.

[0162] Referring to Figure 6 , only one negative electrode tab 1220 extends along the length direction of the negative electrode plate 122. Referring to Figure 7 , negative electrode tabs 1220 extend from both ends along the length direction of the negative electrode plate 122.

[0163] Referring to Figure 8 , only one negative electrode tab 1220 extends along the width direction of the negative electrode plate 122. Referring to Figure 9 , negative electrode tabs 1220 extend from both ends along the width direction of the negative electrode plate 122.

[0164] According to some embodiments of the present application, the electrode assembly further includes a separator, and the porosity of the separator is 20% - 70%. For example, it can be 20%, 30%, 40%, 50%, 60%, 70%, etc., or it can be a range composed of any of the above values. Thus, the transmission efficiency of lithium ions is improved, and the rate performance of the battery cell is improved. According to some embodiments of the present application, the porosity of the separator is 35% - 60%.

[0165] In the present application, the porosity refers to the percentage of the pore volume in the separator membrane occupying the total volume of the separator membrane. The porosity can be tested with reference to the standard GB / T 36363-2018 "Polyolefin Separator for Battery Cells". It should be noted that in the actual testing process, the testing process may be slightly different from the standard according to the differences in testing instruments, testing errors, and in order to eliminate the influence on the porosity test as much as possible, so as to obtain a more accurate test value.

[0166] According to some embodiments of the present application, with reference to Figure 10 , the separator membrane 123 includes: a base film 1231; a first functional layer 1232 located on at least one side of the base film 1231, the first functional layer 1232 including a first inorganic substance; and a second functional layer 1233 located on the side of the first functional layer 1232 away from the base film 1231, the second functional layer 1233 including a second inorganic substance and a non-fluoropolymer. Thereby, the heat resistance of the separator membrane is improved, and the safety of the battery cell is improved.

[0167] According to some embodiments of the present application, the non-fluoropolymer includes an acrylate copolymer. Thereby, the adhesiveness of the non-fluoropolymer is improved, and the risk of the second functional layer peeling off is reduced.

[0168] According to some embodiments of the present application, the first inorganic substance and the second inorganic substance each independently include one or more of silicon oxide, aluminum oxide, boehmite, barium sulfate, calcium oxide, titanium oxide, zinc oxide, magnesium oxide, zirconium oxide, and tin oxide. Thereby, the heat resistance of the separator membrane is improved, and the safety of the battery cell is improved.

[0169] According to some embodiments of the present application, the thickness of the base film is 4 μm - 12 μm. For example, it can be 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, etc., or it can be a range composed of any of the above values. Thereby, while reducing the short circuit between the positive and negative electrodes, the volume occupied by the separator membrane in the battery cell is reduced, and the energy density of the battery cell is improved. According to some embodiments of the present application, the thickness of the base film is 5 μm - 9 μm.

[0170] According to some embodiments of the present application, the battery cell includes a housing and a cover assembly, the cover assembly is disposed at at least one end of the housing, the housing and the cover assembly define a receiving cavity, and the electrode assembly is disposed in the receiving cavity. With reference to Figure 11 , the battery cell includes a housing 11, and the thickness of the housing 111 on the large surface of the battery cell is 0.1 mm - 0.5 mm. Thereby, the energy density of the battery cell is improved.

[0171] According to some embodiments of the present application, the thickness of the housing 111 on the large surface is 0.2 mm - 0.35 mm. Thereby, the energy density of the battery cell is improved.

[0172] According to some embodiments of the present application, the cover plate assembly includes a first cover plate assembly and a second cover plate assembly. The first cover plate assembly and the second cover plate assembly are disposed at two ends in the length direction or the width direction of the housing. The first cover plate assembly includes a first cover plate and a first electrode terminal, and the second cover plate assembly includes a second cover plate and a second electrode terminal. The polarities of the first electrode terminal and the second electrode terminal are opposite. Thereby, during charging, the temperature rise of the battery cell is reduced, and further the impedance of the battery cell is reduced.

[0173] According to some embodiments of the present application, with reference to Figure 12 , the first cover plate assembly includes a first cover plate, a first electrode terminal 131, and a third electrode terminal 133. The polarities of the first electrode terminal 131 and the third electrode terminal 133 are opposite. The second cover plate assembly includes a second cover plate, a second electrode terminal 132, and a fourth electrode terminal 134. The polarities of the second electrode terminal 132 and the fourth electrode terminal 134 are opposite.

[0174] According to some embodiments of the present application, the minimum cross-sectional area of the first electrode terminal and / or the second electrode terminal is S, and 150 mm 2 ≤ S ≤ 1000 mm 2 . Thereby, the overcurrent capacity of the battery cell is improved, the heat generation of the electrode terminal is reduced, the internal resistance of the battery cell is reduced, and the cycle performance of the battery cell is improved.

[0175] In the present application, the minimum cross-sectional area of the first electrode terminal refers to the minimum cross-sectional area along the direction perpendicular to the current flow direction in the first electrode terminal, and the minimum cross-sectional area of the second electrode terminal refers to the minimum cross-sectional area along the direction perpendicular to the current flow direction in the second electrode terminal.

[0176] In the present application, when testing the minimum cross-sectional area of the first electrode terminal and / or the second electrode terminal, it can be calculated according to the shape of the minimum cross-section and its area calculation formula. For example, if the minimum cross-section of the electrode terminal is circular, the minimum cross-sectional area can be obtained by measuring the radius of the circle. If the minimum cross-section is square, the minimum cross-sectional area can be obtained by measuring the length and width of the square.

[0177] As an example, the minimum cross-sectional area S of the first electrode terminal and / or the second electrode terminal can be 150 mm 2 , 300 mm 2 , 450 mm 2 , 600 mm 2 , 750 mm 2 , 900 mm 2 , 1000 mm 2etc., or can be a range composed of any of the above values.

[0178] The battery cell proposed in this application can be used in electrical devices that use the battery cell as a power source or various energy storage systems that use the battery as an energy storage element. The electrical devices can include, but are not limited to, mobile phones, tablets, laptop computers, electric toys, power tools, battery cars, electric vehicles, ships, spacecraft, etc. Among them, the electric toys can include fixed or mobile electric toys, such as game consoles, electric vehicle toys, electric ship toys, and electric aircraft toys, etc., and the spacecraft can include airplanes, rockets, space shuttles, and spaceships, etc.

[0179] The second aspect of this application provides a battery device, including the battery cell provided in the first aspect of this application, and the battery device is one or more of a battery module, a battery pack, and an energy storage device.

[0180] The third aspect of this application provides an electrical device, including the battery cell provided in the first aspect of this application or the battery device provided in the second aspect of this application, and the battery cell or the battery device provides electrical energy for the electrical device.

[0181] The electrical device can include mobile devices (such as mobile phones, laptop computers, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc., but are not limited thereto.

[0182] As the electrical device, the battery device can be selected according to its usage requirements.

[0183] Figure 13 is an electrical device as an example. The electrical device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the high power and high energy density requirements of the electrical device for the battery, a battery pack or a battery module can be used.

[0184] Another example of the device can be a mobile phone, a tablet computer, a laptop computer, etc. This device usually requires thin and light, and a battery cell can be used as a power source.

[0185] To make the technical problems, technical solutions, and beneficial effects solved by the embodiments of this application clearer, the following will further elaborate in detail in combination with the embodiments and the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and in no way constitutes any limitation to this application and its application. Based on the embodiments in this application, all other embodiments obtained by those of ordinary skill in the art without creative efforts belong to the scope protected by this application.

[0186] Embodiment 1 1. Preparation of the positive electrode sheet The positive electrode sheet includes a positive current collector, a positive active material layer, and a positive conductive layer. The positive active material layer is disposed on both sides of the positive current collector, and the positive conductive layer is located between the positive current collector and the positive active material layer. The positive current collector is aluminum foil.

[0187] The positive conductive layer on the positive current collector is a film layer formed by uniformly coating a mixture of a positive conductive agent, superconducting carbon, a positive binder, polyvinylidene fluoride (PVDF), and a solvent, N-methylpyrrolidone (NMP), on the surface of the positive current collector and drying. The thickness is 1 μm, the mass content of the positive conductive agent in the positive conductive layer is 40%, and the mass content of the positive binder is 60%.

[0188] The positive active material layer includes a film layer formed by uniformly coating a positive electrode paste (with NMP as the solvent) on the surface of the positive conductive layer, followed by drying and cold pressing. The positive active material layer includes a positive active material, a binder polyvinylidene fluoride (PVDF), and a conductive agent acetylene black with a mass ratio of 97:2:1.

[0189] The positive active material includes lithium iron phosphate particles and a first coating material. The first coating material coats the surface of the lithium iron phosphate particles. The first coating material includes lithium iron titanium phosphate Li 2 FeTi(PO 4 ) 3 and carbon, and the mass content of carbon element is 1.12%.

[0190] The single-sided coating weight of the positive active material layer is 210 mg / 1540.25 mm 2 .

[0191] The compaction density of the positive active material layer is 2.46 g / cm 3 .

[0192] 2. Preparation of the negative electrode sheet The negative electrode plate includes a negative current collector, a negative active material layer, and a negative conductive layer. The negative active material layer is disposed on both sides of the negative current collector, and the negative conductive layer is located between the negative current collector and the negative active material layer. The negative current collector is a copper foil.

[0193] The negative conductive layer on the negative current collector is a film layer formed by uniformly mixing a negative conductive agent, superconducting carbon, a negative binder, styrene-butadiene rubber (SBR), a thickening agent, sodium carboxymethyl cellulose (CMC-Na), and a solvent, water, and then coating it on the surface of the negative current collector and drying. The thickness is 1 μm. The mass content of the negative conductive agent in the negative conductive layer is 35%, the mass content of the negative binder in the negative conductive layer is 60%, and the mass content of the thickening agent in the negative conductive layer is 5%.

[0194] The negative active material layer includes a film layer formed by uniformly coating a negative electrode paste (with deionized water as the solvent) on the surface of the negative conductive layer and then drying and cold pressing.

[0195] The negative active material layer includes a negative active material, a conductive agent, acetylene black, a negative binder, styrene-butadiene rubber, and a thickening agent, sodium carboxymethyl cellulose, with a mass ratio of 96.5:0.5:2:1. The graphite particles include artificial graphite and a second coating material. The second coating material coats the surface of the artificial graphite, and the mass content of carbon element in the second coating material is 3.5%. The Dv50 of the graphite particles is 11.3 μm.

[0196] The single-sided coating weight of the negative active material layer is 97 mg / 1540.25 mm 2 。

[0197] The compaction density of the negative active material layer is 1.35 g / cm 3 。

[0198] The length of the negative active material layer is 4 mm larger than that of the positive active material layer, and the width of the negative active material layer is 3 mm larger than that of the positive active material layer.

[0199] 3. Separator The separator includes a base film and functional layers disposed on both sides of the base film. The base film includes a polyethylene film layer with a thickness of 7 μm and a porosity of 42%; The functional layer includes a first functional layer and a second functional layer. The first functional layer includes polyacrylate and alumina particles dispersed on the polyacrylate. The first functional layer is a film layer formed by coating a first slurry on one side of the base film, with a thickness of 1 μm, and the average particle size of the alumina particles is 10 nm; among them, the first slurry includes alumina particles and a binder, polyacrylate; The second functional layer is composed of composite particles formed by polyacrylate and polyvinylidene fluoride (PVDF) particles dispersed on the polyacrylate. The second functional layer is a film layer formed by coating the second slurry on the other side of the base film, with a thickness of 5 μm and the average particle size of PVDF particles being 10 nm; the second slurry includes polyacrylate and PVDF particles.

[0200] 4. Preparation of the electrolyte The electrolyte includes an organic solvent, a lithium salt, and an additive.

[0201] After mixing the components of each organic solvent, a lithium salt and an additive are added to prepare the electrolyte.

[0202] The organic solvent includes a first solvent (ethylene carbonate) with a mass ratio of 20%, a second solvent dimethyl carbonate with 31.7%, and a second solvent ethyl methyl carbonate with 28%. The mass content of each component in the organic solvent is calculated based on the mass of the electrolyte.

[0203] The additive includes lithium trifluoroacetate with a mass ratio of 1%, vinylene carbonate VC with 1.5%, fluoroethylene carbonate FEC with 1%, ethylene sulfite ES with 1%, and lithium difluoro(oxalato)borate LiDFOB with 0.8%.

[0204] The lithium salt includes lithium bis(fluorosulfonyl)imide LiFSI with a mass ratio of 5% and lithium hexafluorophosphate LiPF 6 , and the mass content of the lithium salt is calculated based on the mass of the electrolyte.

[0205] 5. Preparation of the battery cell The above positive electrode sheet, separator, and negative electrode sheet are stacked in sequence, with the separator placed between the positive electrode sheet and the negative electrode sheet to play an isolation role, obtaining a stacked electrode assembly. The electrode assembly is placed in a casing, and positive and negative terminals are provided on the casing. After baking, the electrolyte is injected, and through processes such as vacuum packaging, standing, forming, and shaping, the battery cell is obtained.

[0206] The casing is an aluminum shell with a cuboid structure, and the thickness of the casing corresponding to the face with the largest area of the cuboid structure is 0.5 mm.

[0207] Performance testing 1. DC internal resistance DCR test of the battery cell The method of GB / T 31467 "Performance Test Specification for High-Power Lithium-Ion Power Batteries for HEV" can be referred to.

[0208] For example, at room temperature, the battery cell is charged to 3.65 V at a constant current of 0.33 C, then charged at a constant voltage of 3.65 V to 0.05 C, left standing for 30 min, and discharged at a constant current of 0.33 C to 2.0 V, and the discharge capacity A at this time is recorded0 , in Ah, and then charge it at a constant current of 0.33C with 0.5A 0 Ah, and adjust the SOC to 50%.

[0209] After placing the battery cell at -20 °C for 2 h, discharge it at a constant current of 1C for 10 s, and record ∆U 放电 and ∆I 放电 , and obtain the discharge DCR data of the lithium-ion battery through the following formula, R 放电 = ∆U 放电 / ∆I 放电 , where, ∆U 放电 represents the voltage change within 10 s at the start of discharge, and ∆I 放电 represents the current value within 10 s at the start of discharge.

[0210] 2. Cycling performance At 60 °C, charge the battery cell at a constant current of 0.8C to the charge cut-off voltage of 3.6V, then charge it at a constant current of 0.1C to the charge cut-off voltage of 3.65V, and let it stand for 30 min; discharge it at a constant current of 1C to 3.1V, and let it stand for 30 min. This is one charge-discharge cycle. Repeat the above charge-discharge cycle steps until the cycle capacity retention rate (i.e., Cn / C 0 ×100%) is 70%, and record the number of cycles. The more the number of cycles, the better the cycling performance of the battery cell.

[0211] Comparative Example 1 The preparation method of the battery cell is the same as that of Example 1, except that the mass ratio of ethylene carbonate is 15% and the mass ratio of ethyl methyl carbonate is 33%.

[0212] Example 2 The preparation method of the battery cell is the same as that of Example 1, except that the mass ratio of ethylene carbonate is 27.3% and the mass ratio of ethyl methyl carbonate is 20.7%.

[0213] Example 3 The preparation method of the battery cell is the same as that of Example 1, except that the mass ratio of ethylene carbonate is 40% and the mass ratio of ethyl methyl carbonate is 8%.

[0214] Comparative Example 2 The preparation method of the battery cell is the same as that of Example 1, except that the mass ratio of ethylene carbonate is 45% and the mass ratio of ethyl methyl carbonate is 3%.

[0215] The test results of the battery cells in Examples 1 - 3, Comparative Example 1, and Comparative Example 2 are shown in Table 1.

[0216] Table 1

[0217] As can be seen from Table 1, when the contents of the first additive and the second additive are within the protection scope of the present application, by adjusting the content of the first solvent in the electrolyte, the DCR and cycling performance of the battery cell can be adjusted. If the content of the first solvent is too small, although the DCR of the battery cell is small, the cycling life is poor; when the content of the first solvent is too large, the DCR of the battery cell is large and the cycling life of the battery cell is poor. When the content of the first solvent is within the range of 20%-40%, the battery cell can have both a lower DCR and a better cycling life.

[0218] Comparative Example 3 The preparation method of the battery cell is the same as that of Example 2, except that the mass ratio of ethyl methyl carbonate is 21.7%, and the electrolyte does not contain lithium trifluoroacetate.

[0219] Example 4 The preparation method of the battery cell is the same as that of Example 2, except that the mass ratio of ethyl methyl carbonate is 21.6%, and the mass ratio of lithium trifluoroacetate is 0.1%.

[0220] Example 5 The preparation method of the battery cell is the same as that of Example 2, except that the mass ratio of ethyl methyl carbonate is 21.2%, and the mass ratio of lithium trifluoroacetate is 0.5%.

[0221] Example 6 The preparation method of the battery cell is the same as that of Example 2, except that the mass ratio of ethyl methyl carbonate is 19.7%, and the mass ratio of lithium trifluoroacetate is 2%.

[0222] Example 7 The preparation method of the battery cell is the same as that of Example 2, except that the mass ratio of ethyl methyl carbonate is 17.7%, and the mass ratio of lithium trifluoroacetate is 4%.

[0223] Comparative Example 4 The preparation method of the battery cell is the same as that of Example 2, except that the mass ratio of ethyl methyl carbonate is 16.7%, and the mass ratio of lithium trifluoroacetate is 5%.

[0224] The test results of the battery cells in Examples 4 - 8, Comparative Example 3, and Comparative Example 4 are shown in Table 2.

[0225] Table 2

[0226] As can be seen from Table 2, when the first solvent and the first additive are within the protection scope of the present application, by adjusting the content of the second additive, the DCR and cycle life of the battery cell can be regulated. If the electrolyte does not contain the second additive, the trace water contained in the battery cell will hydrolyze lithium hexafluorophosphate, and the generated HF will corrode the SEI film, reducing the cycle performance of the battery cell; if the content of the second additive in the electrolyte is too high, lithium trifluoroacetate has strong acidity and will corrode the aluminum foil, which will also reduce the cycle performance of the battery cell. When the content of the second additive is within the protection scope of the present application, the cycle performance of the battery cell is relatively excellent.

[0227] Comparative Example 5 The preparation method of the battery cell is the same as that of Example 2, except that the mass ratio of ethyl methyl carbonate is 22.7%, the mass ratio of VC is 0.3%, and the mass ratio of FEC is 0.2%.

[0228] Example 8 The preparation method of the battery cell is the same as that of Example 2, except that the mass ratio of ethyl methyl carbonate is 22.2%, the mass ratio of VC is 0.7%, and the mass ratio of FEC is 0.3%.

[0229] Example 9 The preparation method of the battery cell is the same as that of Example 2, except that the mass ratio of ethyl methyl carbonate is 20.2%, the mass ratio of VC is 2.5%, and the mass ratio of FEC is 0.5%.

[0230] Example 10 The preparation method of the battery cell is the same as that of Example 2, except that the mass ratio of ethyl methyl carbonate is 15.2%, the mass ratio of VC is 5%, and the mass ratio of FEC is 3%.

[0231] Comparative Example 6 The preparation method of the battery cell is the same as that of Example 2, except that the mass ratio of ethyl methyl carbonate is 13.2%, the mass ratio of VC is 7%, and the mass ratio of FEC is 3%.

[0232] The test results of the battery cells in Examples 8 - 10, Comparative Example 5, and Comparative Example 6 are shown in Table 3.

[0233] Table 3

[0234] As can be seen from Table 3, when the contents of the first solvent and the second additive are within the protection scope of the present application and are fixed, if the content of the first additive is too small, that is, the total amount of the second additive and the first additive in the electrolyte is relatively small, lithium hexafluorophosphate undergoes hydrolysis to generate HF, resulting in the destruction of the SEI film and poor cycling performance of the battery cell; if the content of the first additive is too large, although the cycling performance of the battery cell is good, the film-forming impedance is large, which will increase the internal resistance of the battery cell and seriously affect the fast charging performance of the battery. With the addition of the second additive in the present application, by adding 1%-8% of the first additive to the electrolyte, the battery cell can have good cycling performance.

[0235] Comparative Example 7 The preparation method of the battery cell is the same as that of Example 2, except that the electrolyte includes ethyl acetate, the mass ratio of ethyl acetate is 39%, the mass ratio of dimethyl carbonate is 15.4%, the electrolyte does not contain ethyl methyl carbonate, and the coating weight of the positive electrode sheet is 263 mg / 1540.25 mm 2 , and the coating weight of the negative electrode sheet is 120 mg / 1540.25 mm 2 .

[0236] Example 11 The preparation method of the battery cell is the same as that of Example 2, except that the electrolyte includes ethyl acetate, the mass ratio of ethyl acetate is 39%, the mass ratio of dimethyl carbonate is 12.9%, the electrolyte does not contain ethyl methyl carbonate, the mass ratio of VC is 2.5%, the mass ratio of FEC is 0.5%, and the coating weight of the positive electrode sheet is 263 mg / 1540.25 mm 2 , and the coating weight of the negative electrode sheet is 120 mg / 1540.25 mm 2 .

[0237] Example 12 The preparation method of the battery cell is the same as that of Example 2, except that the electrolyte includes ethyl acetate, the mass ratio of ethyl acetate is 39%, the mass ratio of dimethyl carbonate is 9.9%, the electrolyte does not contain ethyl methyl carbonate, the mass ratio of VC is 4%, the mass ratio of FEC is 2%, and the coating weight of the positive electrode sheet is 263 mg / 1540.25 mm 2 , and the coating weight of the negative electrode sheet is 120 mg / 1540.25 mm 2 .

[0238] Example 13 The preparation method of the battery cell is the same as that of Example 2, except that the electrolyte includes ethyl acetate, the mass percentage of ethyl acetate is 39%, the mass percentage of dimethyl carbonate is 7.9%, the electrolyte does not contain ethyl methyl carbonate, the mass percentage of VC is 5%, the mass percentage of FEC is 3%, and the coating weight of the positive electrode sheet is 263 mg / 1540.25 mm 2 , and the coating weight of the negative electrode sheet is 120 mg / 1540.25 mm 2 .

[0239] Comparative Example 8 The preparation method of the battery cell is the same as that of Example 2, except that the electrolyte includes ethyl acetate, the mass percentage of ethyl acetate is 39%, the mass percentage of dimethyl carbonate is 5.9%, the electrolyte does not contain ethyl methyl carbonate, the mass percentage of VC is 7%, the mass percentage of FEC is 3%, and the coating weight of the positive electrode sheet is 263 mg / 1540.25 mm 2 , and the coating weight of the negative electrode sheet is 120 mg / 1540.25 mm 2 .

[0240] The test results of the battery cells in Examples 11 - 13, Comparative Example 7, and Comparative Example 8 are shown in Table 4.

[0241] Table 4

[0242] As can be seen from Table 4, the electrolyte can also contain a chain carbonate solvent and a carboxylic acid ester solvent at the same time. When ethyl acetate is contained in the electrolyte, the side reaction between ethyl acetate and graphite is stronger. If the content of the first additive is too small and it cannot participate in film formation, the cycle performance of the battery cell will be poor; if the content of the first additive is too large, although the cycle performance of the battery cell is good, the DCR of the battery cell is large, which is not conducive to fast charging.

[0243] Example 14 The preparation method of the battery cell is the same as that of Example 2, except that the mass percentage of ethyl methyl carbonate is 22.5%, and the electrolyte does not contain sulfur-containing additives and lithium salt additives.

[0244] Example 15 The preparation method of the battery cell is the same as that of Example 2, except that the first solvent includes ethylene carbonate and propylene carbonate, the mass percentage of ethylene carbonate is 22.3%, the mass percentage of propylene carbonate is 5%, and the mass percentage of ethyl methyl carbonate is 20.7%.

[0245] Example 16 The preparation method of the battery cell is the same as that of Example 2, except that the second additive is lithium difluoroacetate.

[0246] Example 17 The preparation method of the battery cell is the same as that of Example 2, except that the second additive is lithium acetate.

[0247] Example 18 The preparation method of the battery cell is the same as that of Example 2, except that the mass ratio of ethyl methyl carbonate is 19.7% and the mass ratio of ES is 2%.

[0248] Example 19 The preparation method of the battery cell is the same as that of Example 2, except that the sulfur-containing additive is vinylene sulfate.

[0249] Example 20 The preparation method of the battery cell is the same as that of Example 2, except that the lithium salt additive is lithium tetrafluoroborate.

[0250] The test results of the battery cells in Examples 14 - 20 are shown in Table 5.

[0251] Table 5

[0252] As can be seen from Table 5, when the contents of the first solvent, the first additive, and the second additive in the electrolyte are within the scope protected by this application, the types and contents of the sulfur-containing additives in the electrolyte and the types of lithium salt additives can be adjusted, and battery cells with better cycle performance and lower DCR can be obtained.

[0253] Finally, it should be noted that: the above embodiments are only used to illustrate the technical solutions of this application, rather than to limit them; although this application has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that: they can still modify the technical solutions recorded in the foregoing embodiments, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of this application, and they should all be covered within the scope of the claims and the description of this application. In particular, as long as there is no structural conflict, the technical features mentioned in each embodiment can be combined in any way. This application is not limited to the specific embodiments disclosed in the text, but includes all technical solutions falling within the scope of the claims.

Claims

1. A battery cell, comprising an electrode assembly and an electrolyte, wherein the electrode assembly comprises a positive electrode sheet, characterized in that: The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes a lithium-containing phosphate; The electrolyte comprises: A first solvent, wherein the first solvent includes one or both of ethylene carbonate and propylene carbonate, and the mass proportion of the first solvent is 20%-40% based on the total mass of the electrolyte; The first additive includes one or two of vinylene carbonate and vinyl carbonate derivatives. Based on the total mass of the electrolyte, the mass proportion of the first additive is 1%-8%, and the vinyl carbonate derivative includes a compound shown in Formula II: Formula II, Wherein, R1, R2, R3, and R4 each independently include any one of a hydrogen atom, a halogen atom, a C1-C5 alkyl group, and a C1-C5 halogenated alkyl group, and R1, R2, R3, and R4 are not hydrogen atoms at the same time; The second additive comprises a compound of formula I: R1-COOLi Formula I, Wherein, R1 includes any one of a hydrogen atom, a halogen atom, a C1-C5 alkyl group, and a C1-C5 halogenated alkyl group, and based on the total mass of the electrolyte, the mass proportion of the second additive in the electrolyte is 0.1%-4%.

2. The battery cell according to claim 1, characterized in that: Based on the total mass of the electrolyte, the mass proportion of the second additive is 0.5%-2%.

3. The battery cell according to claim 1, characterized in that: The second additive includes one or more of lithium acetate, lithium difluoroacetate, and lithium trifluoroacetate.

4. The battery cell according to claim 1, characterized in that: The second additive includes lithium trifluoroacetate.

5. The battery cell according to claim 1, characterized in that: The electrolyte solution further includes a second solvent, and the second solvent includes one or both of a carboxylic acid ester solvent and a chain carbonate solvent.

6. The battery cell according to claim 5, characterized in that: Based on the total mass of the electrolyte, the mass proportion of the second solvent is 45%-65%.

7. The battery cell according to claim 5, characterized in that: The carboxylate solvent includes a compound shown in formula III: Formula III, Among them, R5 includes any one of a hydrogen atom, a halogen atom, a C1-C5 alkyl group, and a C1-C5 halogenated alkyl group, and R6 includes any one of a C1-C5 alkyl group and a C1-C5 halogenated alkyl group.

8. The battery cell according to claim 5, characterized in that: The carboxylate solvent includes one or more of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, and ethyl butyrate.

9. The battery cell according to claim 5, characterized in that: The chain carbonate solvent includes one or more of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

10. The battery cell according to claim 5, characterized in that: When the second solvent includes a linear carbonate solvent, the mass proportion of the first additive is 1%-3% based on the total mass of the electrolyte.

11. The battery cell according to claim 5, characterized in that: The second solvent includes a carboxylate solvent and a chain carbonate solvent. Based on the total mass of the electrolyte, the mass proportion of the carboxylate solvent is 8%-60%, and the mass proportion of the first additive is 3%-8%.

12. The battery cell according to claim 1, characterized in that: The electrolyte further includes a lithium salt, and the lithium salt includes one or both of a fluorinated sulfonyl imide lithium salt and lithium hexafluorophosphate.

13. The battery cell according to claim 12, characterized in that: Based on the total mass of the electrolyte, the mass proportion of the lithium salt is 10%-18%.

14. The battery cell according to claim 12, characterized in that: Based on the total mass of the electrolyte, the mass proportion of the fluorinated sulfonyl imide lithium salt is 4%-6%.

15. The battery cell according to claim 12, characterized in that: The fluorine-containing lithium sulfonyl imide salt includes one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium perfluorobutylsulfonyl imide.

16. The battery cell according to any one of claims 1 to 15, characterized in that: The electrolyte further includes a third additive, and the third additive includes one or more of a sulfur-containing additive and a lithium salt additive.

17. The battery cell according to claim 16, characterized in that: The sulfur-containing additive includes one or more of vinyl sulfate, vinyl disulfate, 1,3-propane sultone, butylene sulfite, vinyl sulfite, and methylene disulfonate.

18. The battery cell according to claim 16, characterized in that: Based on the total mass of the electrolyte, the mass proportion of the sulfur-containing additive is 0-2%.

19. The battery cell according to claim 16, characterized in that: Based on the total mass of the electrolyte, the mass proportion of the sulfur-containing additive is 0.5%-2%.

20. The battery cell according to claim 16, characterized in that: The lithium salt additive includes one or more of lithium difluorophosphate, lithium difluorooxalatoborate, lithium tetrafluoroborate, and lithium bis(oxalatoborate).

21. The battery cell according to claim 16, characterized in that: Based on the total mass of the electrolyte, the mass proportion of the lithium salt additive is 0-1%.

22. The battery cell according to claim 16, characterized in that: Based on the total mass of the electrolyte, the mass proportion of the lithium salt additive is 0.2%-1%.

23. The battery cell according to claim 1, characterized in that: The lithium-containing phosphate comprises: matrix; A first coating material is located on at least a portion of the surface of the substrate, and the first coating material contains carbon.

24. The battery cell according to claim 23, characterized in that: Based on the total mass of the lithium-containing phosphate, the mass proportion of the carbon element is 0.8%-2.3%.

25. The battery cell according to claim 23, characterized in that: The first coating material includes a compound shown in Formula IV: Li 3-d1 Fe 2-d1 M1 d1 (PO m1 ) n1 Formula IV Among them, 0≤d1≤1, 3≤m1≤5, 2≤n1≤4, and M1 includes one or more of Ti, Zr, Hf, Ge, and Sn.

26. The battery cell according to claim 23, characterized in that: The matrix includes a compound shown in Formula V: Li x1 A y1 Me a1 M2 b1 P 1-c1 X c1 Y z1 Formula V Among them, 0.5≤x1≤1.3, 0≤y1≤1.3, 0.9≤x1+y1≤1.3; 0.9≤a1≤1.5, 0≤b1≤0.5, 0.9≤a1+b1≤1.5; 0≤c1≤0.5; 3≤z1≤5; Among them, A includes one or more of Na, K, and Mg; Me includes one or more of Mn, Fe, Co, and Ni; M2 includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X includes one or more of Cl, C, and N; and Y includes one or more of O and F.

27. The battery cell according to claim 23, characterized in that: The matrix includes one or more of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium nickel phosphate, and lithium cobalt phosphate.

28. The battery cell according to claim 1, characterized in that: The compaction density of the positive electrode sheet of the battery cell at 0% charge state is 2.46 g / cm 3 -2.8g / cm 3 .

29. The battery cell according to claim 1, characterized in that: The single-sided coating weight of the positive electrode active material layer is 200 mg / 1540.25 mm 2 -400mg / 1540.25mm 2 .

30. The battery cell according to claim 1, characterized in that The electrode assembly also includes a negative electrode plate, which includes a negative electrode collector and a negative electrode active material layer arranged on at least one side of the negative electrode collector. The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes one or both of a carbon-based material and a silicon-based material.

31. The battery cell according to claim 30, characterized in that: The carbon-based material includes graphite.

32. The battery cell according to claim 31, characterized in that: The graphite is a secondary particle formed by aggregation of primary particles, at least a portion of the surface of the secondary particle has a second coating material, and the second coating material includes amorphous carbon.

33. The battery cell according to claim 32, characterized in that: Based on the total mass of the graphite, the mass proportion of the second coating material is 2%-5%.

34. The battery cell according to any one of claims 31 to 33, characterized in that: The volume average particle size Dv50 of the graphite is 8.5 μm-14.8 μm.

35. The battery cell according to claim 30, characterized in that The negative electrode active material includes a silicon-based material, and based on the total mass of the negative electrode active material layer, the mass proportion of silicon element is 0.3%-5%.

36. The battery cell according to claim 30, characterized in that The single-sided coating weight of the negative electrode active material layer is 90 mg / 1540.25 mm 2 -185mg / 1540.25mm 2 .

37. The battery cell according to claim 30, characterized in that Along the length direction of the battery cell, the size of the negative electrode active material layer is greater than the size of the positive electrode active material layer, and the difference between the size of the negative electrode active material layer and the size of the positive electrode active material layer is OH1; Along the width direction of the battery cell, the size of the negative electrode active material layer is larger than the size of the positive electrode active material layer, and the difference between the size of the negative electrode active material layer and the size of the positive electrode active material layer is OH2, Among them, OH1 is greater than or equal to OH2.

38. The battery cell according to claim 37, characterized in that: 1mm≤OH1≤4mm, 1mm≤OH2≤3mm.

39. The battery cell according to claim 30, characterized in that The positive electrode sheet is provided with a positive electrode tab, and the negative electrode sheet is provided with a negative electrode tab, the positive electrode tab extends along the length direction of the positive electrode sheet or along its width direction; and / or the negative electrode tab extends along the length direction of the negative electrode sheet or along its width direction.

40. The battery cell according to claim 1, characterized in that The electrode assembly further includes a separator having a porosity of 20% to 70%.

41. The battery cell according to claim 40, characterized in that The porosity of the isolation membrane is 35%-60%.

42. The battery cell according to claim 41 or 41, characterized in that: The isolation film comprises: Basement membrane; A first functional layer, located on at least one side of the base film, wherein the first functional layer comprises a first inorganic substance; The second functional layer is located on a side of the first functional layer away from the base film, and the second functional layer includes a second inorganic substance and a non-fluorine polymer.

43. The battery cell according to claim 42, characterized in that The non-fluorine polymer includes an acrylic copolymer.

44. The battery cell according to claim 42, characterized in that The first inorganic substance and the second inorganic substance independently include one or more of silicon oxide, aluminum oxide, boehmite, barium sulfate, calcium oxide, titanium oxide, zinc oxide, magnesium oxide, zirconium oxide, and tin oxide.

45. The battery cell according to claim 42, characterized in that The thickness of the isolation film is 4 μm-12 μm.

46. ​​The battery cell according to claim 42, characterized in that The thickness of the isolation film is 5 μm-9 μm.

47. The battery cell according to claim 1, characterized in that The battery cell comprises a shell and a cover assembly, wherein the cover assembly is arranged at at least one end of the shell, the shell and the cover assembly define a receiving cavity, the electrode assembly is arranged in the receiving cavity, and the shell thickness of the large surface of the battery cell is 0.1mm-0.5mm.

48. The battery cell according to claim 47, characterized in that The shell thickness of the large surface is 0.2mm-0.35mm.

49. The battery cell according to claim 47 or 48, characterized in that: The cover plate assembly includes a first cover plate assembly and a second cover plate assembly, the first cover plate assembly and the second cover plate assembly are arranged at both ends of the length direction or the width direction of the shell, the first cover plate assembly includes a first cover plate and a first electrode terminal, the second cover plate assembly includes a second cover plate and a second electrode terminal, and the polarities of the first electrode terminal and the second electrode terminal are opposite.

50. The battery cell according to claim 49, characterized in that The minimum cross-sectional area of ​​the first electrode terminal and / or the second electrode terminal is S and meets the requirement of 150 mm 2 ≤S≤1000mm 2 .

51. A battery device, characterized in that: Comprising the battery monomer described in any one of claims 1-50, the battery device is at least one of a battery module, a battery pack, and an energy storage device.

52. An electrical device, characterized in that: It comprises the battery cell according to any one of claims 1 to 50 or the battery device according to claim 51, wherein the battery cell or the battery device provides electrical energy for the electrical equipment.

Citation Information

Patent Citations

  • Non-aqueous electrolyte and Li-ion secondary battery, and method for producing them

    CN101212061A

  • Lithium-supplementing electrolyte, lithium-supplementing positive pole piece and lithium ion battery

    CN116960460A

  • Lithium ion battery electrolyte and lithium ion battery

    CN117613386A

  • Winding type lithium ion battery

    CN119275380A

  • Lithium secondary battery

    JP2006179234A